Psychological review - Baldwin, James Mark, 1861-1934; Cattell, James McKeen, 1860-1944; Warren, Howard C. (Howard Crosby), 1867-1934; Watson, John B. (John Broadus), 1878-1958; Langfeld, Herbert Sidney, 1879-1958; Pratt, Carroll C. (Carroll Cornelius), 1894-1979; Newcomb, Theodore M. (Theodore Mead), 1903-1984
Issues for 1894-1903 include the section: Psychological literature.